Can Taiwan be an Example of Successful Promotion of Human Rights in Asia? .......... 335 - Hawang, Shiow-duan (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
This paper starts from the brief history of the democratic transition process of Taiwan. For the past twenty years, the country has peacefully passed the two turnover test, provid-ing relative political freedom and civil liberties for the society. Being the first democratic nation in Chinese society, Taiwan serves as a counter example for those who claim that Eastern values tend to focus on the good of society rather than on the rights of the indi-vidual, and therefore are not suitable for democracy. Through frequent contacts and exchanges between different groups of citizens, Taiwan has gradually become the model to follow. Taiwan’s viable NGOs also provide many experi-ences for other countries to share. Taiwan’s free elections have attracted many visitors to observe and learn. However, Ma’s administration has refrained from playing a more positive role in deal-ing with human rights issues in China. In order to promote their economic interests in China, big entrepreneurs were forced to support pro-China President Ma a few days before the election. Despite all those difficulties, Taiwan has shrewdly positioned itself as a viable alternative when compared with the system of governance in China. In that sense, Taiwan will continue to remain a “thorn” in the side of China as the former presents itself as the democratic alternative alongside its less than democratic neighbour.